Medical English in use : a self-study book with key for doctors and nurses intermediate level - Džuganová, Božena; Poláček, Hubert (Osveta, 2010)
The book contains a variety of medical topics selected from British and American sources (journals, textbooks, newspapers, leaflets etc.).
Keywords: lingvistika, lékařská terminologie; lingvistika; Terminology as Topic; terminologie jako téma; Medicine; Linguistics; lékařství; angličtina